POTENSI WISATA ALAM DESA WONGAYA GEDE - Ni Putu Sri Utami Putri; I Wayan Wijayasa; Ni Ketut Sutrisnawati; Putu Bagus Wisnuwardhana (Jurnal Kajian dan Terapan Pariwisata, 2024)
This research aims to determine the tourism potential in Wongaya Gede Village. This research uses qualitative descriptive analysis techniques supported by qualitative data in the form of natural and cultural potential in Wongaya Gede Village. Primary data in the research are the results of observations regarding the potential at the research location as well as interviews with several sources. Data collection techniques use observation techniques by observing directly at the research location about the existing potential. The data collection method uses 3 methods, namely interviews, documentation and observation. There are 5 tourism potentials in Wongaya Gede Village, the first being Subak Piak, Subak Bengkel, Batukaru Temple, Pikat Waterfall, and Pikat Adventure. From the results of this research, it can be concluded that several natural potentials were found that could be developed as tourist attractions in Wongaya Gede Village, Penebel, Tabanan. Researchers provide suggestions that developing tourism potential needs to pay attention to the potential of existing natural resources to be used as a destination and must look at the facilities provided, apart from that, human resources as managers will also need to be prepared to support the management of tourist destinations.